Relationship Between the Quorum Network (Sensing/Quenching) and Clinical Features of Pneumonia and Bacteraemia Caused by A. baumannii - Fernandez-Garcia, Laura; Ambroa, Antón; Blasco, Lucia; Bleriot, Ines; López, Maria; Alvarez-Marin, Rocio; Fernández-Cuenca, Felipe; Martinez-Martinez, Luis; Vila, Jordi; Rodríguez-Baño, Jesús; Garnacho-Montero, Jose; Cisneros, Jose Miguel; et al. (Frontiers in Microbiology, 2018)
Acinetobacter baumannii (Ab) is one of the most important pathogens associated with nosocomial infections, especially pneumonia. Interest in the Quorum network, i.e., Quorum Sensing (QS)/Quorum Quenching (QQ), in this pathogen has grown in recent years. The Quorum network plays an important role in regulating diverse virulence factors such as surface motility and bacterial competition through the type VI secretion system (T6SS), which is associated with bacterial invasiveness. In the present study, we investigated 30 clinical strains of A. baumannii isolated in the “II Spanish Study of A. baumannii GEIH-REIPI 2000-2010” (Genbank Umbrella Bioproject PRJNA422585), a multicentre study describing the relationship between the Quorum network in A. baumannii and the development of pneumonia and associated bacteraemia. Expression of the aidA gene (encoding the AidA protein, QQ enzyme) was lower (P < 0.001) in strains of A. baumannii isolated from patients with bacteraemic pneumonia than in strains isolated from patients with non-bacteraemic pneumonia. Moreover, aidA expression in the first type of strain was not regulated in the presence of environmental stress factors such as the 3-oxo-C12-HSL molecule (substrate of AidA protein, QQ activation) or H2O2 (inhibitor of AidA protein, QS activation). However, in the A. baumannii strains isolated from patients with non-bacteraemic pneumonia, aidA gene expression was regulated by stressors such as 3-oxo-C12-HSL and H2O2. In an in vivo Galleria mellonella model of A. baumannii infection, the A. baumannii ATCC 17978 strain was associated with higher mortality (100% at 24 h) than the mutant, abaI-deficient, strain (carrying a synthetase enzyme of Acyl homoserine lactone molecules) (70% at 24 h). These data suggest that the QS (abaR and abaI genes)/QQ (aidA gene) network affects the development of secondary bacteraemia in pneumonia patients and also the virulence of A. baumannii.